Analysis of PTPN22, ZFAT and MYO9B polymorphisms in Turner Syndrome and risk of autoimmune disease. (18th June 2017) - Villanueva‐Ortega, E.; Ahedo, B.; Fonseca‐Sánchez, M. A.; Pérez‐Durán, J.; Garibay‐Nieto, N.; Macías‐Galavíz, M. T.; Trujillo‐Cabrera, Y.; García‐Latorre, E.; Queipo, G.
Summary: Turner syndrome (TS) is one of the most common sexual chromosome abnormalities and is clearly associated with an increased risk of autoimmune diseases, particularly thyroid disease and coeliac disease (CD). Single‐nucleotide polymorphism analyses have been shown to provide correlative evidence that specific genes are associated with autoimmune disease. Our aim was to study the functional polymorphic variants of PTPN22 and ZFAT in relation to thyroid disease and those of MYO9B in relation to CD. A cross‐sectional comparative analysis was performed on Mexican mestizo patients with TS and age‐matched healthy females. Our data showed that PTPN22 C1858T (considered a risk variant) is not associated with TS (X 2  = 3.50, p  = .61, and OR = 0.33 [95% CI = 0.10–1.10]). Also, ZFAT was not associated with TS (X 2  = 1.2, p  = .28, and OR = 1.22 [95% CI = 0.84–1.79]). However, for the first time, rs2305767 MYO9B was revealed to have a strong association with TS (X 2  = 58.6, p  = .0001, and OR = 10.44 [95% C = 5.51–19.80]), supporting a high level of predisposition to CD among TS patients. This report addresses additional data regarding the polymorphic variants associated with autoimmune disease, one of the most common complications in TS.